The Charter and Code of the Ordinances of Yazoo City 174, § 297 (1908) - (:unkn) unknown (My University, 1906)
Ch. 20, § 297: It shall not be lawful for any person to sell, give, or lend to any minor or person intoxicated, knowing him to be a minor or in a state of intoxication, any deadly weapon, or other weapon the carrying of which concealed is prohibited, or pistol cartridge; and, on conviction thereof, he shall be punished by a fine of not less than twenty-five dollars nor more than two hundred dollars, or imprisoned not exceeding ninety days, or both.
Keywords: TRANSFER - INCOMPETENTS; TRANSFER - MINORS